The Impact of Ljubljana’s Waste Deposit »Barje« on Groundwater - Joerg Prestor; Mitja Janža (Geologija, 2002)
Ljubljana’s waste deposit is situated on rather thick formation of quaternary sediments on the northern margin of Ljubljansko Barje (Ljubljana Moor). The upper part of quaternary sediments consists of high compressive silty and clayey layers till the depth of aprox. 33 m. These layers are very heterogeneous and one can only find one continuous clayey gravel layer among them at the depth of 8 m and 4 m thick. Below these layers there is the Upper gravel aquifer and from the depth of 72 m there is the Lower gravel aquifer. The bottom of quaternary sediments is aprox. at 140 m depth. The consolidationof highly compressive upper layers and organic compounds from landfill leachate produce the evident impact by reducing conditions in the geological layers below the waste deposit.Though we can detect the reducing conditions also from natural environment in confined layers and rich organic matter content and also from other sources of contamination in the highly urbanized environment. The geometry of the contamination plume was notinvestigated in detail and also not the redox process dynamics. The advection velocities and actual contamination of groundwater are rather low. Further protection measurements will be designed by the aid of the established monitoring results.